2014
DOI: 10.1246/bcsj.20140302
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Catalytic Asymmetric C–C Bond-Forming Reactions to Ketimines Promoted by Metal-Based Catalysts

Abstract: Recent progress (post-2010) in the field of metal-catalyzed asymmetric CC bond-forming reactions using ketimines as electrophiles is reviewed. Compared with the corresponding aldimines, ketimines generally display less inherent reactivity and the two substituents on the imine carbon hamper prochiral-face-selection for enantioselective reactions. Recent advances with newly developed catalytic systems have resulted in several solutions to these long-standing problems. The construction of tetrasubstituted stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 171 publications
0
30
0
Order By: Relevance
“…The direct asymmetric addition of nucleophiles to imines is a highly efficient method for the total synthesis of chiral alkaloids and nitrogen-containing bioactive compounds. [56] Although the Zn-ProPhenol catalyst was originally designed for direct aldol processes, recent studies, especially since 2015, have showed its outstanding ability to react imines with a wide range of nucleophiles, including those that were previously discovered to be inactive towards aldehydes. More importantly, many commonly utilized N-protecting groups are welltolerated, which allows the use of orthogonal protecting group strategies.…”
Section: Catalytic Asymmetric Addition To Iminesmentioning
confidence: 99%
“…The direct asymmetric addition of nucleophiles to imines is a highly efficient method for the total synthesis of chiral alkaloids and nitrogen-containing bioactive compounds. [56] Although the Zn-ProPhenol catalyst was originally designed for direct aldol processes, recent studies, especially since 2015, have showed its outstanding ability to react imines with a wide range of nucleophiles, including those that were previously discovered to be inactive towards aldehydes. More importantly, many commonly utilized N-protecting groups are welltolerated, which allows the use of orthogonal protecting group strategies.…”
Section: Catalytic Asymmetric Addition To Iminesmentioning
confidence: 99%
“…[2] Commensurate with their importance and abundance,n umerous methods have been developed for their preparation, [1,3] among which a prominent approache xploits the enantioselective addition of carbanion equivalents to iminesd erived from prochiral ketones. [4] Ketimines are much more challenging electrophiles than their aldimine counterparts,d ue to their lower electrophilicity and the more difficulte nantiodiscrimination between the two prochiral faces. [4d,e] Nevertheless, in recent years impressive progress in the development of catalytic enantioselective additions of variousp ronucleophiles to ketimines has been made.…”
mentioning
confidence: 99%
“…[4d,e] Nevertheless, in recent years impressive progress in the development of catalytic enantioselective additions of variousp ronucleophiles to ketimines has been made. [4,5] Within this context,o ur group has developed ac ata-lytic system comprising ab asic silver(I) salt and ac inchona-derived aminop hosphine ligand, ableto promote the highly diastereo-and enantioselective addition of isocyanoacetate esters to aldehydes, [6] ketones, [7] and ketimines (Scheme 1a). [8] Wishing to extend the structural diversity of compounds accessible witht his chemistry,w eb ecame interested in expanding the scopeo ft he pronucleophile component.…”
mentioning
confidence: 99%
“…2,3) Thus, the development of synthetic methods for 1-tetrasubstituted-2,2,2-trifluoroethylamines that cannot be accessed by hydrogenation of imines and reductive amination of ketones is an important challenge. 4,5) Catalytic nucleophilic addition to trifluoromethyl ketimines to gain access to these structures has been extensively studied over the last decade (Chart 1, Eq. a).…”
mentioning
confidence: 99%
“…a). 4,5) On the other hand, the reaction of 2,2,2-trifluoroethylamine derivatives with electrophiles is a complementary approach for the synthesis of 1-substituted-2,2,2-trifluoroethylamines (Chart 1, Eq. b).…”
mentioning
confidence: 99%